Maternal CD4+ and CD8+ T Cell Tolerance Towards a Fetal Minor Histocompatibility Antigen in T Cell Receptor Transgenic Mice - PERCHELLET, Antoine L; JASTI, Susmita; PETROFF, Margaret G (Biology of reproduction, 2013)
Tolerance of the maternal immune system in pregnancy is important for successful pregnancy because the semiallogeneic fetus may be subject to antifetal responses. We examined maternal tolerance to the fetus using a murine system in which a model paternally inherited antigen, ovalbumin (OVA), is expressed exclusively in the fetus and placenta. By employing T cell receptor (TCR) transgenic mice specific for major histocompatibility complex class I- or class II-restricted epitopes of OVA (OT-I and OT-II) as mothers, we investigated the fate of fetus-specific CD8⁺ and CD4⁺ T cells, respectively, during gestation. Both OVA-specific CD8⁺ and CD4⁺ T cells displayed an activated phenotype in the peripheral lymphoid tissues of OVA-bred OT-I and OT-II mice, consistent with their encounter of fetal antigen. Whereas a small percentage of OVA-specific CD4⁺ T cells were deleted in the periphery and thymus of OVA-bred OT-II mice, with evidence of TCR downregulation in the remaining T cells, deletion and TCR downregulation were not observed in OVA-bred OT-I mice. Both CD4⁺ and CD8⁺ T cells upregulated inducible costimulator expression in response to the fetal antigen, but only CD4⁺ T cells consistently upregulated the inhibitory receptors programmed cell death 1 and cytotoxic T lymphocyte antigen-4. More regulatory T cells (Tregs) were present in pregnant OVA-bred than in WT-bred OT-II mice, revealing that Tregs expanded specifically in response to the fetal antigen. These data indicate that several mechanisms tolerize fetal antigen-specific maternal CD4⁺ T cells, whereas tolerance of fetal antigen-specific CD8⁺ T cells is less effective. The importance of these mechanisms is underscored by the finding that fetal loss occurs in OVA-bred OT-I but not OT-II mice.